Treatment for Major Depressive Disorder by Repetitive Transcranial Magnetic Stimulation in Different Parameters: A Randomized Double-Blinded Controlled Trial - Zhang, Tingting; Huang, Yueqin; Jin, Yi; Ma, Xiaoyan; Liu, Zhaorui (Frontiers in Psychiatry, 2021)
Background: Repetitive transcranial magnetic stimulation (rTMS) has been proven to be safe and effective in treating major depressive disorder (MDD). However, the treatment parameters of rTMS are still divergent and need to be optimized further. The aim of this study was to compare the efficacy of rTMS in treating MDD with different parameters of stimulating frequency and location, and course of treatment. Methods: A total of 221 patients with MDD were recruited in the randomized, double-blind, controlled trial. All eligible patients were randomly assigned into four treatment groups: (1) 10 Hz in left dorsolateral pre-frontal cortex (DLPFC) (n = 55), (2) 5 Hz in left DLPFC (n = 53), (3) 10 Hz in bilateral DLPFC (n = 57), and (4) 5 Hz in bilateral DLPFC (n = 56). The patients received treatment for 6 weeks and an additional 6-week optional treatment. The efficacies were evaluated by Hamilton Depression Rating Scale-24 items (HDRS) and Clinical Global Impressions Scale (CGI). The trial is registered at the Chinese Clinical Trial Registry as ChiCTR-TRC-12002248. Results: The ANOVAs of HDRS scores up to 6 weeks and 12 weeks with repeated measure of time showed a significant effect of duration without statistical difference among four treatment groups and no significance when time was interacted with inter-group as well. The response rates up until the 5th week were significantly different with the previous week. Conclusions: It concludes that there were no statistical differences in the efficacy of rTMS between unilateral left and bilateral DLPFC, and between 5 and 10 Hz for treating MDD.